Kepraktisan Penggunaan Aplikasi Quizizz Paper Mode Sebagai Media Dalam Evaluasi Pembelajaran Pendidikan Pancasila Kelas V di SD Negeri Lemahireng 05 - Ichsan Abadi; Ahmad Fajar Afrizal; Nur Indah Wahyuni (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Learning evaluation is an important activity in knowing student learning outcomes, therefore an effective media is needed in carrying out evaluation activities. The media that can be used is Quizizz Paper mode which is a technology-based application for evaluating learning. Quizizz with Paper Mode uses a QR code on a piece of paper that can be used in offline learning, aiming to help teachers and students create creative face-to-face learning based on interactive, effective and efficient quizzes. This research was conducted at Lemahireng 05 Public Elementary School with the aim of finding out the practicality of implementing Quizizz paper mode in Civics learning as an evaluation medium. This research uses qualitative methods with data collection techniques in the form of observation and interviews. The results of this research regarding the implementation of learning evaluation using the Quizizz application have proven to be more practical so that evaluation activities become effective and efficient.